Adaptation and Validation of the Indonesian version of the Narcissistic Admiration and Rivalry Questionnaire - Darmawan Muttaqin; Shannen Vania Tanuwijaya; Amabel Kylila; Eunika Putri Kiara Bisowarno; Eunike Kristea Soegianto; Trivia Agatha (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2023)
The Narcissistic Admiration and Rivalry Questionnaire (NARQ) was developed to measure theNarcissistic Admiration and Rivalry concept, as a new process model related to narcissism. This research aimed to adapt and validate the Indonesian version of the NARQ and involved 467 individuals aged 17- 25 years. Confirmatory factor analysis, reliability, and correlation test were used to test the factor structure, internal consistency, and criterion validity of the Indonesian version of the NARQ. The results show that the NARQ has the best factor structure in the form of a two-factor hierarchical model, representing two dimensions and six aspects of narcissistic admiration and rivalry. Also, the Indonesian version of the NARQ is supported by satisfactory reliability and validity criteria. This finding indicates that the Indonesian version of the NARQ is a measuring tool that can be used to assess narcissistic admiration and rivalry in individuals aged 17-25 years in Indonesia.